Generating CRISPR‐Cas9‐Mediated Null Mutations and Screening Targeting Efficiency in Human Pluripotent Stem Cells. Issue 8 (25th August 2021) - Bower, Oliver J.; McCarthy, Afshan; Lea, Rebecca A.; Alanis‐Lobato, Gregorio; Zohren, Jasmin; Gerri, Claudia; Turner, James M.A.; Niakan, Kathy K.
Abstract: CRISPR‐Cas9 mutagenesis facilitates the investigation of gene function in a number of developmental and cellular contexts. Human pluripotent stem cells (hPSCs), either embryonic or induced, are a tractable cellular model to investigate molecular mechanisms involved in early human development and cell fate decisions. hPSCs also have broad potential in regenerative medicine to model, investigate, and ameliorate diseases. Here, we provide an optimized protocol for efficient CRISPR‐Cas9 genome editing of hPSCs to investigate the functional role of genes by engineering null mutations. We emphasize the importance of screening single guide RNAs (sgRNAs) to identify those with high targeting efficiency for generation of clonally derived null mutant hPSC lines. We provide important considerations for targeting genes that may have a role in hPSC maintenance. We also present methods to evaluate the on‐target mutation spectrum and unintended karyotypic changes. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Selecting and ligating sgRNAs into expression plasmids Basic Protocol 2 : Validation of sgRNA via in vitro transcription and cleavage assay Basic Protocol 3 : Nucleofection of primed human embryonic stem cells Basic Protocol 4 : MiSeq analysis of indel mutations Basic Protocol 5 : Single cell cloning of targeted hPSCs Basic Protocol 6 : Karyotyping of targeted hPSCs